2021
DOI: 10.1159/000515443
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of Eruptive Syringoma

Abstract: Syringoma is a benign adnexal tumor of eccrine origin. Eruptive syringoma (ES) is a rare variant and can mimic other diseases especially lichen planus (LP). The dermoscopic observation of ES is not well described. We report here a case of ES, initially misdiagnosed as LP. The dermoscopic findings showed fine reticulate brown lines on a light brown background contrarily to the findings usually seen in LP. These findings prompt a skin biopsy which subsequently confirmed the diagnosis of ES. The use of dermoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Dermoscopic criteria for ES are still under definition [1][2][3]. Mostly, a faint brownish pigmented network on a light brown-to-red background has been reported, presumably reflecting scattered residual melanocytes of the basal epidermal layer [1][2][3]. Also, a reticular vascular network of thin vessels interrupted by hypopigmented areas has been described [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermoscopic criteria for ES are still under definition [1][2][3]. Mostly, a faint brownish pigmented network on a light brown-to-red background has been reported, presumably reflecting scattered residual melanocytes of the basal epidermal layer [1][2][3]. Also, a reticular vascular network of thin vessels interrupted by hypopigmented areas has been described [3].…”
Section: Discussionmentioning
confidence: 99%
“…Eruptive syringoma (ES) is a rare variant of syringoma, a benign adnexal tumor of eccrine sweat glands' ducts, mostly affecting young to middle-aged women [1]. Herein, we present the first case of ES in an elderly woman.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers chose dermoscopy, a non‐invasive method, to verify the characteristic changes. Several studies have indicated that skin lesions appear dermoscopically as brown regular pigmented networks and tiny white spaces between adjacent papules 8,13,14 . Glossy white structures with punctate and linear vessels on a pale pink background are seen in the lesions of the vulvar area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that skin lesions appear dermoscopically as brown regular pigmented networks and tiny white spaces between adjacent papules. 8,13,14 Glossy white structures with punctate and linear vessels on a pale pink background are seen in the lesions of the vulvar area. In contrast, lichen planus, folliculitis, and flat warts can be distinguished from them by their characteristic dermoscopic findings.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients of ES, dermoscopy findings of reticular brown lines or fine pigment networks were described, which is consistent with our patients. Some cases reported that tiny whitish dots, multifocal hypopigmented areas, and glittering yellow-whitish round structures are considered the dermoscopic hallmarks of the vulvar variant [7][8][9]. Histopathological examination showed the presence of epithelial cords, ducts, and cystic structures within the superficial dermis.…”
Section: Es Is Easily Misdiagnosis Clinically and May Be Confused Withmentioning
confidence: 99%